Pengaruh Kepemimpinan terhadap Kinerja Pegawai pada Stasiun Karantina Ikan, Pengendalian Mutu dan Keamanan Hasil Perikanan Bima - Naesa Naesa; Mulyadin Mulyadin (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
In a government organization, the success or failure of government tasks and administration is influenced by leadership. Through leadership and supported by adequate organizational capacity, good governance will be realized. On the other hand, leadership weakness is one of the downfalls in bureaucratic performance in Indonesia (Gede and Priartini 2018).